P10 Investigating the wound healing capacity of outgrowth endothelial cells from diabetic neuropathy and neuroischaemia patients. (26th October 2016) - Weston, R; Hasan, A; Wilkinson, F; Boulton, A; Rashid, T; Bowling, F; Alexander, MY
Abstract : Endothelial dysfunction and inflammation are the most important parameters in the pathogenesis of diabetes, and these processes underpin the development of diabetic foot ulcers. Outgrowth endothelial cells (OECs) have therapeutic potential for diabetic wounds because of their ability to proliferate, migrate and promote angiogenesis. However, the precise mechanisms supporting their differentiation capacity, physiological roles and homing to sites of injury remain to be elucidated. This study aims to establish the function of OECs from diabetic patients with neuroischaemic and neuropathic ulcers, and determine their potential role in wound healing. Healthy volunteer subjects provide OECs as comparative control cells. Migration of CD34+ OECs, evaluated by a scratch assay, demonstrated that migration is impaired in neuropathic OECs compared to healthy control and neuroischaemic OECs. An angiogenesis tube formation assay also established a lack of capacity and reduced capacity of the neuropathic and neuroischaemic OECs respectively to form an endothelial network, compared to healthy OECs measured using the closed loop perimeter, and the number of branch points. Nitrite concentrations measured using a Griess assay, showed that diabetic OECs produced less nitric oxide as compared to healthy OECs. Cytokine analysis of patient serum and OEC supernatant using Bioplex suspension array technology has also been carried out, to determine any correlation between OEC function, the inflammatory and angiogenic profile of the patient. These data are under analysis and will be presented. Understanding these parameters could have great clinical impact in the development of novel wound healing therapies among diabetic patients to reduce ongoing complications.